Misdiagnosis of Cholestasis in a Neonate With Dubin-Johnson Syndrome: A Pre- and Postmortem Report - Sadeghi, Sajjad (Jour Med Resh and Health Sci, 2024)
Dubin–Johnson syndrome (DJS) that commonly known as “black liver disease, is a hereditary disease,” DJS affects individuals of all around the world. This case report explores the challenges involved in diagnosing neonatal cholestasis and emphasizes the importance of considering rare genetic disorders in the differential diagnosis. It describes the clinical experience of a newborn with cholestasis who was initially misdiagnosed with common causes, which unfortunately led to a fatal outcome. Postmortem analysis confirmed Dubin-Johnson syndrome (DJS), a rare hereditary cause of conjugated hyperbilirubinemia. The report highlights the subtle presentation of DJS, atypical hematological disturbances, and the severe systemic impact. This case underscores the need for early genetic testing and a thorough diagnostic approach that considers rare disorders like DJS to improve neonatal outcomes.